FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ORANG PRIBADI TERHADAP ETIKA PENGGELAPAN PAJAK (Studi Empiris pada Wajib Pajak Terdaftar di KPP Pratama Jayapura) - Bryando Helweldery; Theo Allolayuk; Cornelia D. Matani (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This research aims to determine the influence of taxation, tax-service, and taxation sanctions on tax evasion. The population in this research is a registered taxpayer at KPP Pratama Jayapura. Sampling is done according to the proportions, so that the number of respondents are fulfilled by a certain characteristic of 100 respondents. The data analysis methods used in this study are validity, reliability, classical assumption test, hypothesized test and multiple linear regression. The results showed that partially understanding taxation positively affect tax evasion, while the tax authorities have no positive effect and the taxation sanctions have no positive effect on tax evasion In addition, the research has no simultaneous effect on tax evasion at KPP Pratama Jayapura. The implications of this study show that tax evasion is seen as unethical action to do. The Directorate General of Taxation needs to socialize the importance of taxation understanding to lower tax evasion rates.